Duty-Cycle-Aware Minimum Latency Broadcast Scheduling in Multi-hop Wireless Networks - Xianlong Jiao; Wei Lou; Junchao Ma; Jiannong Cao; Xiaodong Wang; Xingming Zhou (2010 IEEE 30th International Conference on Distributed Computing Systems, 2010)
Broadcast is an essential and widely-used operation in multi-hop wireless networks. Minimum latency broadcast scheduling (MLBS) aims to provide a collision-free scheduling for broadcast with the minimum latency. Previous work on MLBS mostly assumes that nodes are always active, and thus is not suitable for duty-cycle-aware scenarios. In this paper, we investigate the duty-cycle-aware minimum latency broadcast scheduling (DCA-MLBS) problem in multi-hop wireless networks. We prove both the one-to-all and the all-to-all DCA-MLBS problems to be NP-hard. We propose a novel approximation algorithm called OTAB for the one-to-all DCA-MLBS problem, and two approximation algorithms called UTB and UNB for the all-to-all DCA-MLBS problem under the unit-size and the unbounded-size message models respectively. The OTAB algorithm achieves a constant approximation ratio of 17|T|, where |T| denotes the number of time-slots in a scheduling period. The UTB and UNB algorithms achieve the approximation ratios of 17|T|+20 and (Δ+22)|T| respectively, where Δ denotes the maximum node degree of the network. Extensive simulations are conducted to evaluate the performance of our algorithms.